Abandonment processes at Middle Bronze Age Erimi: a multi-scalar approach. (10th April 2019) - Amadio, Marialucia; Bombardieri, Luca
Abstract: Abstract : The study of abandonment processes is key to analysing the formation of social identities and the way that these identities are reinforced and maintained through social practices and rituals. Here, preliminary data from Middle Bronze Age Erimi, Cyprus, shed light on abandonment dynamics.